(untitled) - Wells, H. G. (Garden City, 1949)
The Outline of History, subtitled either "The Whole Story of Man" or "Being a Plain History of Life and Mankind", is a work by H. G. Wells that first appeared in an illustrated version of 24 fortnightly installments beginning on 22 November 1919 and was published as a single volume in 1920. It sold more than two million copies, was translated into many languages, and had a considerable impact on the teaching of history in institutions of higher education.
Keywords: World history,Lịch sử thế giới